Inteligência emocional: relação com inteligência, habilidades sociais, variáveis sociodemográficas e profissionais - Peixoto, Isaías (2018)
Emotional Intelligence (EI) is a psychological construct widely broadcasted in the last two decades, especially outside the academic environment. Several studies have been conducted regarding EI, but a larger scientific research framework is needed to consolidate EI as a capacity of intelligence and to demonstrate its relationship with other psychological constructs and variables from daily life. EI may be related to Intelligence (G), Social Skills (HS), gender, age, education, family income and characteristics of the organization environment. Hence, the goal of this research was twofold: first, to study the relationship between EI and G, HS and sociodemographic variables. Second, to investigate EI, G and HS as present in workers in different areas of the organization and in both leaders and non-leaders. As such, the research was divided in two separate studies. The goal of the first study was to analyze the relationship between EI and G, EI and the sociodemographic variables of age, gender, family income, education and EI and HS; the second verified the level of EI, G and HS presented by professionals in different areas and leadership roles in the organizational context. Both studies had the participation of 120 adults, aged 32.16 years in average (SD = 8.82, Md = 31), 84 (70%) men and 36 (30%) women, working in 24 companies in the countryside of the state of São Paulo. They took the Teste Informatizado de Percepção das Emoções Primárias (PEP) and the Teste Informatizado de Compreensão Emocional (TCE) to measure EI; the abstract reasoning and linguistic intelligence modules of the Bateria de Provas de Raciocínio (BPR-5) to check G levels; the Inventário de Habilidades Sociais 2 (IHS2-Del-Prette) and the Sociodemographic and Career Path Survey (Questionário Sociodemográfico e de Carreira Profissional – QSCP). The main results of the first study indicate a weak to positive and moderate correlation between EI and G testing; a moderate and negative correlation between age and emotional perception; a weak and positive correlation between emotional understanding and education and no significant correlation between EI and the HS variables and income. There was also no significant difference between EI scores for men and women. After a linear regression analysis, age and abstract reasoning were shown to be predictors of emotional perception and linguistic intelligence and abstract reasoning were shown to be predictors of emotional understanding. Results from the second study only showed significant differences between professional areas for abstract reasoning in BPR-5 scores; the affective-sexual approach and social resourcefulness, both IHS2-Del-Prette, factors; engineers/technical professionals had the best scores. There was a significant difference between EI scores from leaders and non-leaders. However, professionals in non-leadership jobs had higher scores than leaders, unlike the results found for assertive conversation, a factor in IHS2-Del-Prette in which leaders did better. Research results contributed to show the validity of EI in applied research, since it provided data for a better understanding of how EI is related to HS, how family income is related to EI, and how EI, HS and G are present and how they differ between leaders and non-leaders and among professionals in different work areas.